Survey on Attribute Oriented Induction Using Data Mining Techniques - Radha Priya, S; Devapriya, M (International Journal of Computer Sciences and Engineering, 2025)
Data and objects in databases often contain detailed information at primitive concept levels. It is useful to summarize a large set of data and present it at a high conceptual level. Attribute Oriented Induction(AOI) is a set-oriented data base mining method which generalizes the task-relevant subset of data attribute-by-attribute compresses it into a generalized relation and extracts from it the general features of data. The power of AOI is extraction from relational databases of different kinds of patterns including characteristic rules, discriminant rules, cluster description rules and multilevel association rules. The method is efficient, robust with wide applications and extensible to knowledge discovery in advanced database systems, including object-oriented, deductive and spatial database systems. This paper describes the broad classification of data mining techniques using AOI.